CARRIAGE OF MULTI-DRUG RESISTANT UROBACTERIA BY ASYMPTOMATIC PREGNANT WOMEN IN YENAGOA, BAYELSA STATE, NIGERIA - Onanuga, Adebola; Omeje, Maureen Chinelo; Eboh, Darlington Deboh (African Journal of Infectious Diseases (AJID), 2018)
Background: Urinary Tract Infections (UTIs) in pregnancy are associated with significant morbidity for both mother and baby but its early detection and treatments can prevent unfavorable complications in pregnancy. This study therefore determined the prevalence of asymptomatic bacteriuria and antimicrobial resistance profile of the urinary bacteria among pregnant women in Yenagoa, Bayelsa State, Nigeria. Materials and Methods: Mid-stream urine samples were collected from 201 apparently healthy pregnant women attending antenatal clinics in Yenagoa. The samples were analyzed and the organisms identified using standard microbiological methods. Haemolysin production by the organisms was screened and their antimicrobial susceptibility was performed using standard assay methods. Results: A high significant bacteriuria of 119 (59.2%) was predominantly recovered from the pregnant women in their second and third trimesters. The bacteria isolated; Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli and Staphylococcus species had 36 – 67% of haemolysin producers. The bacteria exhibited a very high resistance to most of the antibiotics tested but the resistance to ceftazidime, gentamicin and ciprofloxacin was 28 – 67%. All the Staphylococcus species exhibited 90% and 85% resistance to cefoxitin (methicillin resistant) and vancomycin respectively. An 89 - 100% of the bacteria exhibited multiple antibiotic resistance and 72.3% of the screened bacteria phenotypically expressed Extended-Spectrum Beta-lactamase production. Conclusion: The high prevalence of significant bacteriuria with high multi-drug resistance among the study pregnant women call for regular education on proper personal hygiene and the need for early screening for UTIs during antenatal clinics as means of controlling the spread of antibiotic resistant organisms and complications in pregnancy.